A critical appraisal on artificial intelligence: common law and Sharī‘ah - Mohd. Zain, Nor Razinah; Yusof, Siti Ainatul Mardhiah (2020)
The disruption of innovations through technology in the society continues to indicate a positive trend among users at large. The innovations of technology that stand with speediness and fast track transaction effectively support the spread in using such smart devices without barriers of time and space. Recently, the world continues to be surprised with the latest technology’s innovation that is known as artificial intelligence or can be simple known as A.I. By looking into the ecosystem for future sustainability of legal principles from both Common Law and Sharī‘ah, an evaluation on the use of A. I. should be scrutinized especially with the continuous increase of its usage and dependency in the modern system. This research will look into the position of A.I. and its acceptability from Common Law and Sharī‘ah. It is found that Sharī‘ah never rejects any application of technology, including A.I. While, Common Law is struggling to develop their legal principles specifically relating to A.I., Sharī‘ah has a matured collective legal principles in accepting A.I.